FAKTOR-FAKTOR YANG MEMPENGARUHI PREDIKSI ARUS KAS MASA DEPAN PADA PERUSAHAN MANUFAKTUR SEKTOR KONSUMSI - Susan Susanti; Trismayarni Elen (Unversitas Prof. Dr. Moestopo (Beragama), 2021)
The objective of study is to analyze to determine the effect of earnings, receivables, and cash flow on the prediction of future cash flows. The financial statements are considered as a measurement that is considered very important in seeing the company's achievements. Financial statements are seen as a tool that is able to reduce uncertainty in making economic decisions for users, one way to reduce uncertainty is to conduct an analysis of the financial statements. The population in this study are all consumption sector manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the 2014-2018 period. The reason for choosing a manufacturing sector manufacturing company is homogeneity considerations in the main income earning activities. In addition, manufacturing companies in the consumption sector are more stable compared to other companies on the IDX. Based on the results of data analysis and discussions that have been carried out (1) Income has a significant effect on the prediction of future cash flows, (2) Significant receivables from future cash flow predictions and (3) Cash flows from operating activities do not significantly affect the prediction of future cash flows.